Credit Risk Management: A Case Study on Maybank Automobile Financial Services - Bentan, Ghazalli (2011)
A non performing loan is a loan which is either in default or is about to be, with a reasonable expectation that the loan will enter default even though it has not technically defaulted yet. As a general rule, banks prefer to avoid non performing loan because there is a risk mainly credit risk that they will not be able to recover the principal left on the loan, let alone the interest which has accrued. In hire purchase, the facility is 'fragile' in nature due to its extensive exposure to credit risk issues such as weak income gross level, weak net disposable income, high financing margin, financing of non popular model, high risk job sector, high risk business sector and fraudulent transactions. This dissertation is a case study on Maybank Automobile Financial Services non-performing loans problems. From the case study we find some essential factors that contributed to the increasing default trend over the study period. The existence and implementation of Standard Practice Instruction (SPI), Credit Policy and Guidelines from relevant authority sometimes were 'ignored' by staff or branches due to branches' robust business appetite to secure larger market share in vehicle financing. The issue is also due to information asymmetry leading to incomplete documentation and lack of information. This has worsened the credit risk and operational risk situation. The study traces strategies taken to manage the high non performing loan rate and identifies more effective approaches taken by the bank to address the risks involved. The case study reveals that it is of utmost importance to adopt a strong credit risk management culture through the practice of continuous, comprehensive and integrated approach in order to uphold high standard of credit underwriting.